Is Moral Education Effective in Preventing Radicalism and Terrorism? - Ariyani, Sri Dewi (Faculty of Law Universitas Negeri Semarang, 2023)
Pancasila is a solution to the problem of radicalism that is currently plaguing Indonesia. So it is hoped that the values in Pancasila must really be carried out by the people of Indonesia in order to prevent and minimize radicalism and terrorism in our beloved country. The loss of the values contained in Pancasila in Indonesian society is the root of the emergence of various acts of radicalism and terrorism in Indonesia. Therefore, the implementation of Pancasila values, in order to remain actual in facing the threat of radicalism, must place more emphasis on conveying three messages, namely, first, this country was formed based on agreement and equality, in which no one should feel that he is the main shareholder, or citizen. first class. Second, the rules of the game within the state have been agreed upon, and the state has full sovereignty to discipline its state members who are trying systematically to change the order, in ways that are against the law. Third, the state provides protection, opportunity, future and balanced protection to achieve the national goals of a just and prosperous, secure, civilized and independent society. The Indonesian government has recently begun to be wary of the development of radicalism in the country in relation to the ISIS (Islamic State of Iraq and Syria) network. The issue of ISIS has become a global issue and it seems that the world is united to fight it. Seeing this phenomenon, steps need to be taken to prevent radicalism from thriving in this motherland. In addition to taking action against the perpetrators of radicalism, the government must also take preventive or preventive measures so that people are not easily provoked by ideologies that use religious attributes. Close cooperation is needed between the government, security forces and religious leaders to straighten out religious understanding.